Orientasi Filosofis Hakim Pengadilan Agama Dalam Menyelesaikan Sengketa Ekonomi Syariah - Zaidah Nur Rosidah; Lego Karjoko (Fakultas Hukum Universitas Islam Indonesia, 2021)
The purpose of this study is to determine the philosophical basis in the legal finding school of thoughts used by religious court judges and their orientation in resolving sharia economic disputes. The research problem is answered by using a normative method with a case and conceptual approach. The results of the research and discussion conclude that first, sharia economic dispute resolution has a philosophical foundation from the values of Pancasila, especially the first, second and fifth principles. Second, there are two different orientations of religious court judges in deciding sharia economic disputes, namely legism oriented and begriffjurisprudenz orientation. Amongst the various decisions, there are judges that are still oriented towards legism, namely deciding disputes based on existing positive laws, based on the Civil Code (KUHPer) even though the dispute is a sharia economic dispute. There are also many judges who have an orientation to begriffjurisprudenz, in this case the judge uses the basis of Islamic law, namely the Al Quran, Hadith and the Fatwa of the National Sharia Council (DSN) of the Indonesian Ulama Council (MUI) and the Compilation of Sharia Economic Law (KHES) in their decisions in addition to using the Civil Code (positive law).